2012
DOI: 10.1097/scs.0b013e31825dad6c
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Primary Monocanalicularnasal Intubation With Monoka Tubes and Nasal Endoscopic Findings for Congenital Nasolacrimal Duct Obstruction With Enlarged Lacrimal Sac and Chronic Dacryocystitis

Abstract: In cases of CNLDO with an enlarged lacrimal sac and chronic dacryocystitis, monocanalicular intubation is recommended rather than simple probing. Monoka tube intubation has the advantages of technical ease of insertion and tube removal. Moreover, the tubing does not threaten the unprobed part of the lacrimal drainage system. Endoscopic findings revealed that the probe tip protruded through a balloon-like nasal mucosa with pus around the Hasner valve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Other non-randomized studies comparing stenting to probing as a primary procedure were likewise rated weak; Eshraghi et al found a significantly higher success rate (73.3% vs. 48.9%) in the Masterka stent group compared with the probing group in children older than 18 months [27], while Al-Faky et al noted a success rate of 88% for stenting and 80.3% for probing [28]. In general, intubation has been found to have an advantage over probing alone in certain groups, such as those with bilateral congenital NLDO, Down syndrome, history of acute dacryocystitis, and other causes of complex NLDO [28,59,60].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other non-randomized studies comparing stenting to probing as a primary procedure were likewise rated weak; Eshraghi et al found a significantly higher success rate (73.3% vs. 48.9%) in the Masterka stent group compared with the probing group in children older than 18 months [27], while Al-Faky et al noted a success rate of 88% for stenting and 80.3% for probing [28]. In general, intubation has been found to have an advantage over probing alone in certain groups, such as those with bilateral congenital NLDO, Down syndrome, history of acute dacryocystitis, and other causes of complex NLDO [28,59,60].…”
Section: Discussionmentioning
confidence: 98%
“…This systematic review observed that lacrimal intubation is most commonly performed as a primary procedure in children with congenital NLDO, with good outcome. It is preferred over probing alone in complex NLDO [28,59,60]. Up to approximately ten years old, age is not predictive of intubation failure [32,61].…”
Section: Discussionmentioning
confidence: 99%
“…For complete sac decompression, monocanalicular intubation with pus drainage by manual compression over the lacrimal sac fossa and antibiotic irrigation is more effective than simple probing. 16 Further study about the different causes of CNLDO based on patient ethnicity are needed.…”
Section: Discussionmentioning
confidence: 99%